Досудове розслідування на деокупованих територіях: нормативне врегулювання та перспективи здійснення - Фоміна, Т. Г.; Fomina, T. H.; Тетяна Фоміна (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 2 (105), ч. 2. - С. 136-148, 2024)
Досліджено стан нормативно-правового регулювання порядку здійснення досудового розслідування, а також з’ясовано його перспективи після деокупації українських територій. Проведено аналіз законопроєктів, які регулюють процедуру здійснення кримінального провадження в післявоєнний період. Особливу увагу приділено питанню оцінки отриманих окупаційною владою доказів та наведено аргументи на користь позиції щодо недопустимості таких доказів.

The state of normative regulation of the pre-trial investigation procedure was studied, as well as the prospects for its implementation after the de-occupation of Ukrainian territories were clarified. It was emphasized that the raised issue requires qualitative discussion by representatives of various institutions of criminal justice. It is important in this direction to build effective algorithms for pre-trial investigation bodies, the prosecutor’s office, the court, which cannot be implemented without the introduction of new legislative initiatives. Based on the analysis of the state of normative and legal regulation, it was found that currently, at the level of current criminal procedural legislation, the issue of the fate of criminal proceedings after de-occupation has not been settled. The issue of the procedure for carrying out criminal proceedings in which materials are lost, in particular destroyed in the occupied territory, is also not defined. Currently, there are draft laws (in particular, prepared by the Office of the Prosecutor General and the Ukrainian Helsinki Human Rights Union), which can be taken into account when improving the legislation in this direction. Currently, there are many questions regarding the procedure for conducting pre-trial investigations in the de-occupied territories. In particular, this is a question of evaluating the evidence obtained by the occupation authorities; terms in criminal proceedings that were initiated by national bodies of pre-trial investigation and were not completed at the time of occupation; restoration of lost materials of criminal proceedings. Special attention is paid to the issue of evaluation of the evidence obtained by the occupation authorities and arguments are given in favor of the position regarding the inadmissibility of such evidence. The necessity of standardizing the procedure for restoring (full or partial) lost materials of criminal proceedings (both materials of pre-trial investigation and materials of court proceedings) has been proven.

Исследовано состояние нормативно-правового регулирования порядка осуществления досудебного расследования, а также установлены его перспективы после деоккупации украинских территорий. Проведен анализ законопроектов, регулирующих процедуру осуществления уголовного производства в послевоенный период. Особое внимание уделено вопросу оценки полученных доказательств оккупационными властями и приведены аргументы в пользу позиции относительно недопустимости таких доказательств.
Pre-trial investigation in the de-occupied territories: normative regulation and prospects for implementation
Keywords: кримінальне провадження; досудове розслідування; докази; процес доказування; допустимість доказів; деокупація; перехідне правосуддя; criminal proceedings; pre-trial investigation; evidence; evidence process; admissibility of evidence; de-occupation; transitional justice; уголовное производство; досудебное расследование; доказательства; процесс доказывания; допустимость доказательств; деоккупация; переходное правосудие